Role of the Honorary Commission for the Fight against Tuberculosis and Prevalent Diseases (CHLA-EP) in the National Vaccination Strategy against COVID-19 in Uruguay: November 2020 - July 2021 (Archives of Pediatrics of Uruguay, 2023)
The new Coronavirus SARS CoV-2 pandemic was declared at the beginning of March 2020 when the Uruguayan government appointed the National Contingency Plan for the COVID-19 disease caused by this virus. This plan included non-pharmacological preventive measures such as: hand hygiene, physical distancing, use of different types of masks according to the risk of who should wear them, in some periods, restrictions to mobility, educational activities or public shows, and movement by land, air or sea. Responsible freedom was strongly called for. In December 2020, the Vaccination Strategy was included as a primary prevention mechanism. On 3/1/2021, the COVID-19 2021 Vaccination Campaign began, it was non-mandatory, population-based, initially for people over 19 years of age, and for adolescents between 12 and 17 years of age and pregnant women since June. The National Honorary Scientific Advisory Group (GACH) together with the National Vaccine Advisory Committee (CNAV) of the Ministry of Public Health (MSP) that has vast experience in advising health authorities in scientific decisions on the introduction of vaccines, and an ad-Hoc Commission created for COVID-19 vaccines, brought together experts to advise on the vaccination strategy. The Honorary Commission for the Fight Against Tuberculosis and Prevalent Diseases (CHLA-EP), as the operational branch of the MSP’s Department of Immunizations, has participated with all stakeholders since December to implement the COVID-19 Population Vaccination Campaign without neglecting their tasks regarding the vaccination to prevent other infectious diseases.Methodology: a descriptive, retrospective study was carried out regarding the strategies implemented by the Immunization Operational Department (operational branch of the Ministry of Health’s Immunization Department), A. Calmette Laboratory, Honorary Commission, General Coordination and Administrative Departments between November, 2020 and July 2021.Data source: reports were issued or provided specially for this work by the Immunization Operational Department, A. Calmette Laboratory, by the Ministry of Public Health’s immunization Department, Human Resources, Material Resources, Support, Communication and Design Service, Peripheral Centers, Executive Board and General secretariat.Results: the results of the 4 periods are as follows: 1- Planning (Period November - December 2020), 2- Training, hiring of human resources and advice for the acquisition of qualitative and quantitative material resources (January - February 2021), 3- Opening of COVID-19 vaccination centers (Hubs), posts and launch of the COVID-19 Campaign (March 2021), 4- Overlap of the 2021 flu campaign (April-June) and maintenance of vaccine coverage (National Immunization Programme - PNI).Conclusion: the planning, training, provision of human and material resources has enabled us to successfully carry out two historical simultaneous vaccination campaigns in hubs, vaccination centers, ELEPEM and all along the territory.
Keywords: Pandemics; SARS-CoV-2; COVID-19; Contingency plans; COVID-19 vaccines; Vaccination strategy